When the jessamine grows - Everhart, Donna (Kensington Publishing Corp, 2024)
"An evocative, morally complex novel set in rural 19th century North Carolina, as one woman fights to keep her family united, her farm running, and her convictions whole during the most devastating and divisive period in American history"--